2010
DOI: 10.1021/ma9027257
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Hairy Particles and Antifouling Films Using Brush-Type Amphiphilic Block Copolymer Surfactants in Emulsion Polymerization

Abstract: Two series of well-defined brush-type amphiphilic block copolymers of polystyrene-b-poly-[poly(ethylene glycol) methyl ether methacrylate] (PS-b-P(PEGMA300) and PS-b-P(PEGMA1100)) were synthesized via atom transfer radical polymerization (ATRP) and used as surfactants in emulsion polymerization. The self-assembly behavior of these block copolymers in aqueous solution was studied by dynamic light scattering and cryogenic transmission electron microscopy. The critical micelle concentration of the synthesized pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 78 publications
5
95
0
Order By: Relevance
“…The possibility exists to introduce responsive behavior to parameters such as pH [3][4][5], temperature [6,7] or UV irradiation [2]. The versatility in properties has resulted in an increased attention in the last decades for application in several fields including smart materials [6,7], micro emulsion stabilization [8] and polymerization [9,10], coatings [11], drug delivery [12][13][14] and enhanced oil recovery [2,3,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility exists to introduce responsive behavior to parameters such as pH [3][4][5], temperature [6,7] or UV irradiation [2]. The versatility in properties has resulted in an increased attention in the last decades for application in several fields including smart materials [6,7], micro emulsion stabilization [8] and polymerization [9,10], coatings [11], drug delivery [12][13][14] and enhanced oil recovery [2,3,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] Previously we demonstrated that hybrid amphiphilic block copolymers comprising a hydrophilic glycosylated polypeptide block and a hydrophobic polystyrene block could efficiently stabilise styrene latex formation. [36][37][38] Previously we demonstrated that hybrid amphiphilic block copolymers comprising a hydrophilic glycosylated polypeptide block and a hydrophobic polystyrene block could efficiently stabilise styrene latex formation.…”
Section: Synthesis Of Glycosylated Block Copolypeptidesmentioning
confidence: 99%
“…Polymer‐grafted polymeric microspheres have attracted continuing interests due to their potential applications in coating, bioseparation, molecular imprinting, Pickering emulsion, organic/inorganic composite, and biomedical analysis . One important advantage of polymer‐grafted polymeric microspheres is the possibility to include certain functional groups on the shell periphery.…”
Section: Introductionmentioning
confidence: 99%
“…This is a more straightforward and efficient approach to prepare polymer‐grafted polymeric microspheres with relatively low density of grafted polymers. A large number of functional polymers (e.g., block copolymer and macromonomer) have been explored to synthesize polymer‐grafted polymeric microspheres by emulsion polymerization, precipitation polymerization, and dispersion polymerization . Despite the tremendous progress made in this research area, many challenges still remain to be addressed.…”
Section: Introductionmentioning
confidence: 99%